PENGARUH MODEL PEMBELAJARAN DISCOVERY LEARNING LEARNINGTERHADAP KEMAMPUAN PEMAHAMAN KONSEP MATEMATIKA PESERTA DIDIK KELAS XI MIPA SMAN 2 PADANG - Deva Martha (Departemen Matematika, 2021)
One of the goals of mathematics learning is to understand mathematical concepts, namely competence in explaning the interrelationships between concept and using concepts and algorithm in a flexible, accurate, efficient, and precise way in problem solving in Permendikbud Number 58 of 2014. However, based on the results of observations in SMAN 2 Padang showed the understanding of mathematical concepts of class XI is still relatively low. Efforts to overcome these problems are to apply the Discovery Learning (DL) learning model to improve the understanding of mathematical concepts. The purpose of the research is to find the ability to understand mathematical concepts of students whose learning with DL models is better than the ability to understand it whose learning with the application of conventional learning models in XI MIPA SMAN 2 Padang. This tipe of research is a quasi-experimental study with static group design. The population of this study was students of XI MIPA SMAN 2 Padang with research samples were XI MIPA 5’s students as experimental classes and class XI MIPA 4’s students as control classes. While the sample technique is random sampling. The research instrument is the final tes of understanding mathematical concepts. Based on the analysis seen that on the results of the final test hypothesis with α=0.05 obtained P−value=0.018 which means reject H0. It can be conclude that there is an influence on the application of DL model to the understanding of mathematical concepts of students of class XI MIPA SMAN 2 Padang. Keywords –Discovery Learning, Mathematical understanding concept